Russia : Towards Improving the Efficiency of Public Investment Expenditures - World Bank (Washington, DC, 2013)
This report documents the current levels and patterns of public investment in Russia, analyzes the institutional arrangements in place for investment budgeting, and develops short- and medium-term recommendations where policy or institutional strengthening is required for improving the efficiency of investment expenditures. The analysis of public investment is based primarily on the federal government though some issues of subnational investment budgeting are also touched upon In any case, many of the issues and recommendations at the federal level are likely to have relevance for subnational investment budgeting also. While the Government is embarked upon overall budgetary reforms, the special characteristics of multi-year investment programs require special attention in the face of evidence of inefficiencies in the use of public funds for investment purposes, improvements in their efficiency--both in terms of their allocation across sectors and activities, and in terms of their cost-effectiveness--are clearly important. It is also clear that many gains would come from the strengthening of the institutional arrangements for investment budgeting--in the areas of budget preparation, implementation, and ex post evaluation and accountability.